173k views
5 votes
Solve the equation: 6(3x - 4) + 54 = -3(x + 11)

User Gandolfa
by
5.5k points

1 Answer

5 votes

Answer:

x = -3

Explanation:

6(3x-4) + 54 = -3(x+11)

18x-24+54 = -3x-33 Multiply 3x and -4 by 6 this means distributive

property. Next, multiply x and 11 by -3.

18x+30 = -3x-33 Next, combine -24 and 54 which equals 30.

-30 -30 Next, subtract 30 from both sides to leave 18x by itself.

18x = -3x-63

+3x +3x Next, add 3x to both sides to leave -63 by itself.

21x = -63

/ /

21 21 Divide 21 on both sides to leave x by itself.

x = -3

User Lakshmana Kumar D
by
4.0k points